Thyroid hormones dynamics during early development in freshwater catfish, Heteropneustes fossilis (Bloch) - Nayak, P K; Satpathy, B B; Mishra, T K; Ayyappan, S (Indian Journal of Fisheries, 2011)
Changes in the concentrations of thyroid hormones in the eggs, embryonicdevelopment and larvae of fi-eshwater catfish (Heteropneustes fossilis) were analyzedusing radioimmimoassay. Results showed that both thyroxin(T^) and triiodothyronineCTg)were present in significant quantities in fertilized eggs. There was a steady decrease inboth T^ and Tg levels during embryonic development. The level continued to decline afterhatching until around third day, when most of the yolk had been absorbed. The T^ levelstarted increasing prior to completion of yolk absorption, suggesting that the larvalthjToid gland had begun to produce T^ (onset of thyroxinogenesis). The hormoneconcentration increased further in 17-day old larvae, which coincided with the metamorphictransformation of larvae to juveniles (19-21 days post larvae), indicating role of thyroidhormones in metamorphic transformation of freshwater catfish, //. fossilis